Direct in situ observation of increasing structural dimensionality during the hydrothermal formation of open-framework zinc phosphates. - Walton, R; Norquist, A; Neeraj, S; Natarajan, S; Rao, C; O'Hare, D (2001)
The first time-resolved in situ X-ray diffraction studies of the hydrothermal crystallisation of open-framework zinc phosphates reveal a pathway of sequential crystallisation involving formation of a metastable low dimensional chain phase before the growth of three-dimensional zeolitic architectures.